AESTHETIC NEGATIVITY VS. ECONOMIC NATURALISM: A CLOSE READING OF AN INDIAN AI-ART PRACTICE - Ponnachan, Anoop Daniel; Rajawat, Anupriya; Gupta, Jaynat Kumar; Purohit, Megha Attray (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This article examines the inherent tension present in AI-based art, specifically addressing whether critical engagement can endure once these practices become part of systems of visibility that prioritise novelty, technological differentiation, and quick consumption. Taking Harshit Agrawal’s The Anatomy Lesson of Dr. Algorithm (2018), Masked Reality (2019), and Strange Genders (2020) as its primary case studies, it reads the works through close visual and interpretive analysis in relation to Adorno, Han, Baudrillard, and Gawronski. Its concern is not if and simply that the works engage technology, but how aesthetic critique is actually carried in them, through form, installation, and interactivity, or else shifted into curatorial framing and digital presence. What emerges unevenly across them is that the work is strongest where classification, simulation, and archival identity are felt as aesthetic pressure than when established in advance. Where that pressure weakens, novelty and circulation begin to come too much into the forefront. The question, then, is not simply whether AI-based art can be critical, but what conditions still allow it to remain resistant.